Optical coherence tomography-guided stenting of a large coronary aneurysm: images at implantation and at 6 months. - Adlam, D; Hutchings, D; Channon, K (2011)
Intravascular imaging with optical coherence tomography (OCT) can produce high-resolution images (10-20 μm) of the coronary vessel wall and is being increasingly used to provide insight into coronary pathology and neointima formation following coronary stenting. Fourier domain OCT (FD-OCT) permits a greater scan diameter than time domain OCT and enables larger-caliber coronary structures to be effectively imaged. We present a case of a large, symptomatic and expanding right coronary artery aneurysm treated with FD-OCT-guided pericardial covered stenting and describe the OCT findings immediately after stent deployment and at 6 months.